Cancer‐linked genetic testing: Growing panels and challenges in the United States: In this first of a two‐part series, genetic testing is promising more targeted approaches to prevention and intervention for hereditary cancers, but new recommendations are running up against communication challenges and differences even within the United States. Issue 12 (12th December 2022) - Nelson, Bryn; Faquin, William
Abstract : This news section is written by a medical journalist and offers Cancer Cytopathology readers timely information on events, issues, and personalities of interest to the subspecialty. In this issue, the first of a two‐part series, genetic testing promises more targeted approaches to prevention and intervention for hereditary cancers, but communication issues and differences even within the United States are creating challenges.